Interconnection of psycho-physiological indicators and performance in running at 100 m at athletes of high qualification with visual impairment (for example an elite athlete). - Zh.L. Kozina; O.I. Chaika (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
The purpose of the work is to theoretically and experimentally substantiate the influence of psychophysiological factors on individual performance in athletics sprint in high-qualified athletes on the example of an elite athlete. Material and methods. Participants. The study involved a high-qualified athlete, specializing in short-distance running and long jump among athletes with visual impairments (category T12). The course of the study. Individual characteristics of the psychophysiological state and results in running for 100 m for five months were analyzed. Results. A theoretical concept of the regulation of the running speed of the nervous system in athletes with visual impairment is developed. Athletes with visual impairment are more difficult than healthy athletes to develop the maximum running speed because of the blockage of speed from the central nervous system. Partial or complete solution of this problem lies in the activation of compensatory mechanisms in the absence of visual function. With the development of psycho-physiological functions characteristic of a particular person, compensatory mechanisms develop to reduce the lack of a visual analyzer.The models of multiple linear regression between results in 100m run for an elite sportswoman with visual impairment and psychophysiological indices are compiled. High importance of psychophysiological indices in individual performance in running on 100 m is shown. Conclusions. Compensatory mechanisms of visual function deficiency were established to maintain high speed in the 100 m run as psychophysiological functions: indicators characteristic of sprinters (speed of simple reaction and motility of the nervous system) and specific indicators (efficiency, strength of the nervous system).